Evolution of Glaucoma Surgery in the Last 25 Years - Laura Bar-David (Rambam Maimonides Medical Journal, 2018)
Glaucoma is a chronic neurodegenerative optic nerve disease. Treatment is intended to prevent the development and progression of optic nerve damage by lowering intraocular pressure (IOP). Current therapy options include topical/systemic drugs that increase aqueous humor outflow or decrease its production, laser therapy that targets the trabecular meshwork and ciliary body, and incisional surgery. Trabeculectomy as well as glaucoma drainage devices are often performed, given their high efficacy in lowering IOP. However, the significant risk profile with potential sight-threatening complications has motivated glaucoma experts to create alternative surgeries to treat glaucoma. Minimally invasive glaucoma surgery (MIGS) is defined by: micro-invasive approach, minimal tissue trauma, high safety profile, and rapid recovery. The new devices might promote an earlier transition from medical/laser therapy to surgery, and therefore decrease the side effects associated with long-term use of topical medications as well as deal with the limited adherence of patients to their regimens. This review presents the surgical options available for glaucoma patients and their evolution over the past 25 years.